Comparison of plateletpheresis on the Fenwal Amicus, Fresenius COM.TEC, and Trima Accel Cell separators. Issue 3 (17th September 2014) - Keklik, Muzaffer; Eser, Bulent; Kaynar, Leylagul; Sivgin, Serdar; Keklik, Ertugrul; Solmaz, Musa; Ozturk, Ahmet; Buyukoglan, Ruksan; Yay, Mehmet; Cetin, Mustafa; Unal, Ali
Abstract : Blood component donations by apheresis have become more common in modern blood transfusion practices. We compared three apheresis instruments (Fenwal Amicus, Fresenius COM.TEC, and Trima Accel) with regard to platelet (PLT) yield, collection efficiency (CE), and collection rate (CR). The single‐needle or double‐needle plateletpheresis procedures of the three instruments were compared in a retrospective, randomized study in 270 donors. The blood volume processed was higher in the COM.TEC compared with the Amicus and Trima. Also there was a significantly higher median volume of ACD used in collections on the COM.TEC compared with the Amicus and Trima. The PLT yield was significantly lower with the COM.TEC compared with the Amicus and Trima. Additionally, the CE was significantly lower with the COM.TEC compared with the Amicus and Trima. There was no significant difference in median separation time and CR between the three groups. When procedures were compared regarding CE by using Amicus device, it was significantly higher in single‐needle than double‐needle plateletpheresis. When double‐needle Amicus system was compared with double‐needle COM.TEC system, CE and PLT yield were significantly higher with Amicus system. When single‐needle Amicus system was compared with single‐needle Trima system, CE and PLT yield were significantly higher with Trima system. All instruments collected PLTs efficiently. However, the CE was lower with the COM.TEC compared with the Amicus and Trima. Also, we found Amicus single‐needle system collected PLTs more efficiently compared with the double‐needle system. CE and PLT yields were significantly higher with the single‐needle Trima instrument compared with the single‐needle Amicus device. J. Clin. Apheresis 30:171–175, 2015. © 2014 Wiley Periodicals, Inc.